1997
DOI: 10.1128/iai.65.11.4620-4623.1997
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine secretion by human polymorphonuclear granulocytes after stimulation with Mycobacterium tuberculosis and lipoarabinomannan

Abstract: Macrophages (MAC) and polymorphonuclear granulocytes (PNG) are professional phagocytes which perform essential functions in antibacterial defense. The intracellular bacterium Mycobacterium tuberculosis persists and replicates in resting macrophages. Although it is generally assumed that activated MAC are central to protection against M. tuberculosis, PNG may also contribute to defense. We wondered whether PNG produce proinflammatory chemokines after stimulation by M. tuberculosis or its major cell wall compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(32 citation statements)
references
References 15 publications
3
27
0
2
Order By: Relevance
“…1), suggesting that, by this function, they may amplify both the innate and the adaptive immune response [16]. For example, neutrophils cultured with either Mycobacterium tuberculosis or lipoarabinomann (its major cell wall component) have been shown to release CXCL1 and CXCL8 [34], two chemokines involved in neutrophil recruitment. Similarly, neutrophils release CXCL8 when exposed in vitro to Candida albicans [35], Helicobacter pylori water soluble surface protein [36] and H. pylori neutrophil-activating protein (HP-NAP) [37].…”
Section: Human Neutrophilsmentioning
confidence: 99%
“…1), suggesting that, by this function, they may amplify both the innate and the adaptive immune response [16]. For example, neutrophils cultured with either Mycobacterium tuberculosis or lipoarabinomann (its major cell wall component) have been shown to release CXCL1 and CXCL8 [34], two chemokines involved in neutrophil recruitment. Similarly, neutrophils release CXCL8 when exposed in vitro to Candida albicans [35], Helicobacter pylori water soluble surface protein [36] and H. pylori neutrophil-activating protein (HP-NAP) [37].…”
Section: Human Neutrophilsmentioning
confidence: 99%
“…Highlighting the importance of virulence factors for the outcome of infection, a study showed that in primary human neutrophils, only virulent Mtb could survive the host-generated respiratory burst by inducing necrotic cell death (Corleis et al, 2012). After stimulation with Mtb, neutrophils secrete chemokines and pro-inflammatory cytokines leading to recruitment and activation of other immune cells (Riedel and Kaufmann, 1997). Human apoptotic neutrophils infected with Mtb can be phagocytosed by Mtb-infected macrophages; in this case, the anti-microbial contents of neutrophil granules can directly fuse with Mtb-containing phagosomes in macrophages, leading to improved killing (Tan et al, 2006).…”
Section: Innate Defences To Mtb In the Airways: Recruited Defendersmentioning
confidence: 99%
“…Another chemokine produced by phagocytic cells and tissue cells after simulation with MTb or its products is IL‐8 (171–173). Increased levels of IL‐8 are seen in the bronchoalveolar lavage fluid of humans with TB infection, and proportionately higher levels of IL‐8 may be associated with increased mortality (174, 175).…”
Section: Chemokines: Ccl2 and Il‐8mentioning
confidence: 99%